Bidirectional OFDM-WDM-PON System Employing 16-QAM Intensity Modulated OFDM Downstream and OOK Modulated Upstream - El-Nahal, Fady (Photonics Letters of Poland, 2016)
We have investigated an orthogonal frequency-division multiplexing (OFDM) wavelength-division-multiplexing (WDM) passive optical network (PON) with centralized lightwave and direct detection. The system was demonstrated for both 10 Gbps 16 quadrature amplitude modulation (16-QAM) intensity-modulated OFDM downstream signals and 2.5 Gbps On-off keying (OOK) upstream signals respectively. A wavelength-reuse scheme is employed to carry the upstream data by using a mach-zehnder modulator (MZM) as an intensity Modulator at the optical network unit (ONU). The proposed scheme offers a promising solution for future PONs. Full Text: PDF References Elaine Wong, "Next-Generation Broadband Access Networks and Technologies", J. Lightwave Technol. 30(4), 597 (2012). CrossRef F.T. An, D. Gutierrez, K.S. Kim, J.W. Lee, L.G. Kazovsky, "SUCCESS-HPON: A next-generation optical access architecture for smooth migration from TDM-PON to WDM-PON", IEEE Commun. Mag. 43(11), S40 (2005). CrossRef S.-J. Park, C.-H. Lee, K.-T. Jeong, H.-J. Park, J.-G. Ahn, K.-H. Song, "Fiber-to-the-home services based on wavelength-division-multiplexing passive optical network", J. Lightwave Technol. 22, 2582 (2004). CrossRef C.W. Chow, C.H. Yeh, "Using Downstream DPSK and Upstream Wavelength-Shifted ASK for Rayleigh Backscattering Mitigation in TDM-PON to WDM-PON Migration Scheme", IEEE Photon. J. 5(2), 7900407 (2013). CrossRef J. Yu, M.-F. Huang, D. Qian, L. Chen, G.-K. Chang, "Centralized Lightwave WDM-PON Employing 16-QAM Intensity Modulated OFDM Downstream and OOK Modulated Upstream Signals", IEEE Photon. Technol. Lett. 20(18), 1545 (2008). CrossRef C.W. Chow, "Wavelength Remodulation Using DPSK Down-and-Upstream With High Extinction Ratio for 10-Gb/s DWDM-Passive Optical Networks", IEEE Photon. Technol. Lett. 20(1), 12 (2008). CrossRef W. Hung, C.-K. Chan, L.-K. Chen, F. Tong, "A bit-serial optical packet label-swapping scheme using DPSK encoded labels", IEEE Phot. Techn. Lett. 15(10), 1630 (2003). CrossRef N. Deng, C.K. Chan, L.K. Chen, "A centralized-light-source WDM access network utilizing inverse-RZ downstream signal with upstream data remodulation", Opt. Fiber Technol. 13, 18 (2007). CrossRef G. Talli, C.W. Chow, E.K. MacHale, P.D. Townsend, "Rayleigh noise mitigation in long-reach hybrid DWDM-TDM PONs", J. Opt. Networking 6, 765 (2007). CrossRef N. Cvijetic, "OFDM for Next-Generation Optical Access Networks", J. Lightwave Techn. 30(4), 384 (2012). CrossRef D. Qian, N. Cvijetic, J. Hu, T. Wang, "108Gb/s OFDMA-PON with Polarization Multiplexing and Direct-Detection", Tech. Dig. OFC 2009, paper PDPD5 (2009). CrossRef D. Qian, N. Cvijetic, Y.-K. Huang, J. Hu, T. Wang, "100km long reach upstream 36Gb/s-OFDMA-PON over a single wavelength with Source-Free ONUs", Tech. Dig. ECOC 2009, paper PD3.3 (2009). DirectLink M. Huang, D. Qian, N. Cvijetie, "A novel symmetric lightwave centralized WDM-OFDM-PON architecture with OFDM-remodulated ONUs and a coherent receiver OLT". DirectLink T. Dong, Y. Bao, Y. Ji, A. Lau, Z. Li, C. Lu, "Bidirectional Hybrid OFDM-WDM-PON System for 40-Gb/s Downlink and 10-Gb/s Uplink Transmission Using RSOA Remodulation", IEEE Photonics Technol. Lett. 24(22), 2024 (2012). CrossRef A. Chahine, U. Okonkwo, R. Ngah, "Study the performance of OFDM radio over fiber for wireless communication systems", IEEE International RF and Microwave Proceedings, 335-338 (2008). CrossRef D. Qian, J. Yu, J. Hu, L. Zong, L. Xu, T. Wang, "8x11.5-Gbit/s OFDM transmission over 1000 km SSMF using conversional DFB lasers and direct- detection", in OFC, San Diego, CA, Paper OMM3 (2008). DirectLink B.J. Schmidt, A.J. Lowery, J. Armstrong, "Experimental demonstrations of 20 Gbit/s direct-detection optical OFDM and 12 Gbit/s with a colorless transmitter", in OFC, Anaheim, CA, Paper PDP18 (2007). DirectLink Y.C. Chung, "Recent advancement in WDM PON technology", Tech. Dig. ECOC 2011, Geneva, Paper Th.11.C.4 (2011) CrossRef J.M. Kang, S.K. Han, "A novel hybrid WDM/SCM-PON sharing wavelength for up- and down-link using reflective semiconductor optical amplifier", IEEE Photon. Technol. Lett. 18(3), 502 (2006). CrossRef C.H. Yeh, C.W. Chow, H.Y. Chen, J.Y. Sung, Y.L. Liu, " Demonstration of using injection-locked Fabry-Pe?rot laser diode for 10?Gbit/s 16-QAM OFDM WDM-PON", Electron. Lett. 48(15), 940 (2012). CrossRef C. Lei, M. Chen, H. Chen, S. Yang, S. Xie, "A Colorless ONU Scheme for WDM-OFDM-PON with Symmetric Bitrate and Low-cost Direct-detection Receivers", Lasers and Electro-Optics (CLEO) 2015, pp. 1 - 2, (2015). CrossRef OptiSystem Package from Optiwave.